2019
DOI: 10.21037/tlcr.2019.07.03
|View full text |Cite
|
Sign up to set email alerts
|

Treatment modes for EGFR mutations in patients with brain metastases from non-small cell lung cancer: controversy, causes, and solutions

Abstract: Brain metastasis from non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations is a hot research topic, but also a difficulty in targeted NSCLC therapy, and is also the focus of controversy in the field of lung cancer treatment. According to medical oncology, asymptomatic patients were initially treated with targeted therapy, followed by local radiotherapy when symptoms present or disease progresses. However, from the perspective of the discipline of radiotherapy, brain metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…Platinum compounds (cisplatin and carboplatin) and pemetrexed, alone or in combination (etoposide, paclitaxel, and radiotherapy) are the most commonly used chemotherapy regimens against BMs from NSCLC (Mehta et al, 2010 ; Barlesi et al, 2011 ; Bailon et al, 2012 ; Shi et al, 2017 ; Yousefi et al, 2017 ; Franchino et al, 2018 ). Since about 33% of patients with non-small cell lung cancer (NSCLC) and EGFR mutations develop BMs, different generations of tyrosine kinase inhibitors (TKIs) were commonly used to target BMs (Burel-Vandenbos et al, 2013 ; Sekine and Satoh, 2017 ; Zhuang et al, 2019 ). Gefitinib is the most typical first-generation TKI and AZD3759 is characterized by its strong ability to effectively penetrate the BBB (Tan et al, 2017 ; Hochmair, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Platinum compounds (cisplatin and carboplatin) and pemetrexed, alone or in combination (etoposide, paclitaxel, and radiotherapy) are the most commonly used chemotherapy regimens against BMs from NSCLC (Mehta et al, 2010 ; Barlesi et al, 2011 ; Bailon et al, 2012 ; Shi et al, 2017 ; Yousefi et al, 2017 ; Franchino et al, 2018 ). Since about 33% of patients with non-small cell lung cancer (NSCLC) and EGFR mutations develop BMs, different generations of tyrosine kinase inhibitors (TKIs) were commonly used to target BMs (Burel-Vandenbos et al, 2013 ; Sekine and Satoh, 2017 ; Zhuang et al, 2019 ). Gefitinib is the most typical first-generation TKI and AZD3759 is characterized by its strong ability to effectively penetrate the BBB (Tan et al, 2017 ; Hochmair, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence has revealed that patients with BM could benefit from targeted therapy and immunotherapy. 8 , 9 Therefore, we identified patient subgroups stratified by survival outcomes based on the patientā€™s intrinsic characteristics that were associated with the combination of treatment strategies. Patients wild type for mutations aside from radiotherapy underwent treatment with mono-chemotherapy according to guidelines for elderly people.…”
Section: Discussionmentioning
confidence: 99%
“…This goal may be achieved with the introduction of novel targeted systemic agents including tyrosine kinase inhibitors and checkpoint inhibitors. However, these agents are mainly used for patients with non-small cell lung cancer (NSCLC) rather than for patients with SCLC (10)(11)(12)(13)(14). For patients with cerebral metastases from SCLC, WBI alone still is the most frequently used type of treatment, particularly for elderly patients who may not be able to tolerate novel systemic agents that can cause considerable side effects including severe inflammatory reactions (5).…”
Section: Discussionmentioning
confidence: 99%